Change in Portal Pressure and Clinical Outcome in Cirrhotic Patients with Gastric Varices after Plug-Assisted Retrograde Transvenous Obliteration - Park, Jae Woo; Yoo, Jeong-Ju; Kim, Sang Gyune; Jeong, Soung Won; Jang, Jae Young; Lee, Sae Hwan; Kim, Hong Soo; Lee, Jae Myung; Shim, Jong Joon; Kim, Young Don; Cheon, Gab Jin; Jun, Baek Gyu; et al. (Gut and liver, 2020)
Plug-assisted retrograde transvenous obliteration (PARTO) is widely used to manage gastric varices with a portosystemic shunt. It is not clear whether portal pressure and the incidence of complications increase after PARTO. The aim of this study was to determine the changes in portal pressure and the associated changes in liver function, ascites, hepatic encephalopathy, and especially esophageal varix (EV) after PARTO. From March 2012 to February 2018, 54 patients who underwent PARTO were analyzed retrospectively. The parameters collected included liver function and episodes of cirrhotic complications before and at 1 and 6 months after PARTO. The analysis of 54 patients showed improvement in liver function during the 6-month follow-up period (Model for End-Stage Liver Disease score: change from 11.46±4.35 to 10.33±2.96, p=0.021). Among these 54 patients, 25 patients were evaluated for their hepatic venous pressure gradient (HVPG) before and after PARTO (change from 12.52±3.83 to 14.68±5.03 mm Hg; p<0.001). Twenty-five patients with portal pressure measured before and after PARTO were evaluated for risk factors affecting liver function improvement and EV deterioration. No factor associated with portal pressure was affected by liver function improvement. Post-PARTO portal pressure was a risk factor affecting EV deterioration (HVPG-post: odds ratio, 1.341; 95% confidence interval, 1.017 to 1.767; p=0.037). The artificial blockade of the portosystemic shunt evidently leads to an increase in HVPG. Liver function was improved over the 6-month follow-up period. Portal pressure after PARTO was a significant risk factor for EV deterioration. Portal pressure measurement is helpful for predicting the patient's clinical outcome.